A systematic review of enteric dysbiosis in chronic fatigue syndrome/myalgic encephalomyelitis - Du Preez, S.; Corbitt, M.; Cabanas, H.; Eaton, N.; Staines, D.; Marshall-Gradisnik, S. (Systematic reviews, 2018)
Background Chronic fatigue syndrome or myalgic encephalomyelitis (CFS/ME) is an illness characterised by profound and pervasive fatigue in addition to a heterogeneous constellation of symptoms. The aetiology of this condition remains unknown; however, it has been previously suggested that enteric dysbiosis is implicated in the pathogenesis of CFS/ME. This review examines the evidence currently available for the presence of abnormal microbial ecology in CFS/ME in comparison to healthy controls, with one exception being probiotic-supplemented CFS/ME patients, and whether the composition of the microbiome plays a role in symptom causation. Methods EMBASE, Medline (via EBSCOhost), Pubmed and Scopus were systematically searched from 1994 to March 2018. All studies that investigated the gut microbiome composition of CFS/ME patients were initially included prior to the application of specific exclusion criteria. The association between these findings and patient-centred outcomes (fatigue, quality of life, gastrointestinal symptoms, psychological wellbeing) are also reported. Results Seven studies that met the inclusion criteria were included in the review. The microbiome composition of CFS/ME patients was compared with healthy controls, with the exception of one study that compared to probiotic-supplemented CFS/ME patients. Differences were reported in each study; however, only three were considered statistically significant, and the findings across all studies were inconsistent. The quality of the studies included in this review scored between poor (< 54%), fair (54–72%) and good (94–100%) using the Downs and Black checklist. Conclusions There is currently insufficient evidence for enteric dysbiosis playing a significant role in the pathomechanism of CFS/ME. Recommendations for future research in this field include the use of consistent criteria for the diagnosis of CFS/ME, reduction of confounding variables by controlling factors that influence microbiome composition prior to sample collection and including more severe cases of CFS/ME.